Neuromodulation to guide circuit reorganization with regenerative therapies in upper extremity rehabilitation following cervical spinal cord injury - Balbinot, Gustavo (Frontiers in Rehabilitation Sciences, 2024)
Spinal cord injury (SCI) is a profoundly debilitating condition with no effective treatment to date. The complex response of the central nervous system (CNS) to injury and its limited regeneration capacity pose bold challenges for restoring function. Cervical SCIs are the most prevalent and regaining hand function is a top priority for individuals living with cervical SCI. A promising avenue for addressing this challenge arises from the emerging field of regenerative rehabilitation, which combines regenerative biology with physical medicine approaches. The hypothesis for optimizing gains in upper extremity function centers on the integration of targeted neurorehabilitation with novel cell- and stem cell-based therapies. However, the precise roles and synergistic effects of these components remain poorly understood, given the intricate nature of SCI and the diversity of regenerative approaches. This perspective article sheds light on the current state of regenerative rehabilitation for cervical SCI. Notably, preclinical research has yet to fully incorporate rehabilitation protocols that mimic current clinical practices, which often rely on neuromodulation strategies to activate spared circuits below the injury level. Therefore, it becomes imperative to comprehensively investigate the combined effects of neuromodulation and regenerative medicine strategies in animal models before translating these therapies to individuals with SCI. In cases of severe upper extremity paralysis, the advent of neuromodulation strategies, such as corticospinal tract (CST) and spinal cord stimulation, holds promise as the next frontier in enhancing the effectiveness of cell- and stem cell-based therapies. Future preclinical studies should explore this convergence of neuromodulation and regenerative approaches to unlock new possibilities for upper extremity treatment after SCI.